Organizational and economic mechanism of regulation of international educational migration - Reznik, Nadiia; Fedun, Igor; Smutchak, Zinaida; Petukhova, Olga; Artamonova, Galina (My University, 2020)
The article considers the peculiarities of migration processes in Ukraine. Attention is focused on the trends of educational migration. The positive and negative consequences of educational migration for recipient countries and donor countries have been identified. The purpose of the article is to reveal the features of modern educational migration, in particular in Ukraine, as an urgent problem of higher education, to identify its features, consequences and identify the main measures to ensure its regulation. Organizational and economic bases of the mechanism of management of educational migration are developed, formation of which is impossible without building active cooperation of the basic subjects - institutional bodies of the state, employers, establishments, public organizations, youth volunteer organizations and associations and able-bodied young citizens entering the market of educational services, and later on the labor market (based on a survey conducted to identify the level of potential educational migrants). В статті розглядаються особливості міграційних процесів в Україні. Увага акцентована на тенденціях прояву освітньої міграції. Виявлено позитивні та негативні наслідки освітньої міграції для країн-реципієнтів та країн-донорів. Мета статті полягає у розкритті особливостей сучасних освітніх міграцій, зокрема в Україні, як актуальної проблеми функціонування вищої освіти, виявленні її особливостей, наслідків та виявленні основних заходів щодо забезпечення її регулювання. Розроблено організаційно-економічні засади механізму управління освітньою міграцією, формування якого неможливе без побудови активної співпраці основних суб’єктів – інституційних органів держави, роботодавців, установ, громадських організацій, молодіжних волонтерських організацій та об’єднань і працездатних молодих громадян, які виходять на ринок освітніх послуг, а згодом і на ринок праці (на основі проведеного соціологічного дослідження, з метою виявлення рівня потенційних освітніх мігрантів).
Keywords: кафедра маркетингу; demographic potential; migration; educational migration; higher education institutions; educational mobility; демографічний потенціал; міграція; освітня міграція; вищі навчальні заклади; освітня мобільність; кафедра міжнародної економіки